Pharmacognostic standardization and quality control of stem bark of Cinnamomum cassia (L.) J.Presl - Devi, Usha; Ahmed, Anees; Ansari, Shoeb Ahmed; Sattar Khan, Asma; Meena, Rampratap (Asian Journal of Pharmaceutical Research and Development, 2024)
Cinnamomum cassia (L.) J.Preslstem bark is one of the most popular spice used for cooking as well as in traditional and modern medicines. C.cassiais a tree of tropical region of Lauraceae family, commonly known as Chinese cinnamon. Bark has been used as anti-inflammatory, analgesic, antioxidant, antimicrobial, anti-obesity, mosquito larvicidal, anti-diabetic, antitumour, anti-tyrosinase activity and cardiovascular protective.Traditionally, it is used to cure dental problems, oral microbiota, and bad breath.In Indian traditional medicine, especially in Unani and Ayurveda, the bark is used medicinally to treat a various of illnesses, including diarrhoea, kidney pain, cough & cold, cobra bite, headaches, acne, dysuria, burning micturition, indigestion, weakness of liver, amenorrhea, fungal infection, weakness of liver and for the management of sexual dysfunction. Pharmacognostic studies help to validate crude drugs and set standardization parameters that can assist in the prevention of adulteration. The present study will help to set the specific macro-microscopicand physico-chemical parameters to identity C. cassia stem bark which certainly assurance the quality of crude drug and will definitely help in standardization of various traditional herbal formulations containing C.cassia stem bark as ingredient.